Identifikasi Senyawa Metabolit Sekunder Pada Rumput Laut Coklat (Sargassum plagyophyllum) Dengan Metode Fraksinasi - Fatma Eka Putri; Andarini Diharmi; Rahman Karnila (Agricultural Faculty, 2023)
Seaweed has potential as a source of bioactive compounds, food and medicine. One of the seaweeds that has the potential to be used for its bioactive compounds is the brown seaweed Sargassum plagyophyllum. Fractionation is a technique of separating and grouping the chemical content of extracts based on their polarity. This study aims to determine the bioactive components (secondary metabolites) of flavonoids, alkaloids, steroids/terpenoids, saponins and phenols qualitatively and quantitatively from the extract of S. plagyophyllum by fractionation method. The research method used was experimental. S. palgyiophyllum was extracted using the fractionation method. The treatment given by different polarity solvents consisted of methanol, was done fractionation with using n-hexane, ethyl acetate, and butanol. Extraction of samples the first used methanol, after that methanol extract was diffracted with n-hexane, ethyl acetate and butanol. Parameter analysis was consisted of phytochemical test (qualitative analysis) and quantitative analysis of total phenol, flavonoid, and saponin content. The results showed that qualitative testing of the secondary metabolites of S. plagyophyllum contained in the methanol extract were steroids/terpenoids, saponins and phenols, the positive hexane fraction contained steroids/terpenoids, saponins, the ethyl acetate fraction positively contained alkaloids, flavonoids, steroids/terpenoids, and saponins. and phenol while the butanol fraction contains steroids/terpenoids, saponins. While quantitative secondary metabolites were tested on the hexane fraction (0.18% saponins), then the ethyl acetate fraction (0.14% flavonoids, 0.11% saponins, 0.12% total phenol) and butanol fraction (0.05% saponins).